Perkembangan Penerapan Sumpah Mubahalah Dalam Hukum Pidana Di Indonesia - Khoiri Akhmadi; Holijah Holijah (PSHPM Untag Semarang, 2026)
The Mubahalah Oath and Corruption are interrelated issues that require a comprehensive and collaborative response from all sectors of society. The concept of the Mubahalah Oath serves as a powerful reminder of the consequences of corruption and criminal acts. Eradicating corruption and promoting transparency and accountability are believed to create a more just and equal society for all. By dismantling the systems that perpetuate corruption, we can build a society based on integrity, justice, and respect for all individuals. This paper discusses a literature review on the Mubahalah Oath and corruption in the development of criminal law in Indonesia. The Extended Systematic Literature Review approach, namely a systematic search for references based on scientific research and expanded with public information, is used in searching for related references to be analyzed. The results show that the Mubahalah Oath can play an important role in eradicating corruption in Indonesia. Implementing the Mubahalah Oath, moral pressure for corruptors, and a tool to strengthen transparency and accountability in government and organizations. The implementation of the Mubahalah Oath can have a positive impact on eradicating corruption and creating better governance in Indonesia. Promoting a culture of honesty and accountability as a first step in eradicating corruption can pave the way for a brighter future for law enforcement in the future